2014
DOI: 10.1155/2014/201436
|View full text |Cite
|
Sign up to set email alerts
|

Withania coagulansFruit Extract Reduces Oxidative Stress and Inflammation in Kidneys of Streptozotocin-Induced Diabetic Rats

Abstract: The present study was carried out to investigate the changes in oxidative and inflammatory status in streptozotocin-induced diabetic rat's kidneys and serum following treatment with Withania coagulans, a popular herb of ethnomedicinal significance. The key markers of oxidative stress and inflammation such as inflammatory cytokines (IL-1β, IL-6, and TNF-α) and immunoregulatory cytokines (IL-4 and IFN-γ) were increased in kidneys along with significant hyperglycemia. However, treatment of four-month diabetic rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 29 publications
4
24
0
Order By: Relevance
“…30) Prolonged ROS leads to renal dysfunction and histologic real injury. 31) The histopathology result of this study confirmed the renal damage in diabetic mice as clear pathological changes were observed. UDCA managed to prevent this damage, confirming the renoprotective effect through ER stress blocker.…”
Section: )supporting
confidence: 78%
See 1 more Smart Citation
“…30) Prolonged ROS leads to renal dysfunction and histologic real injury. 31) The histopathology result of this study confirmed the renal damage in diabetic mice as clear pathological changes were observed. UDCA managed to prevent this damage, confirming the renoprotective effect through ER stress blocker.…”
Section: )supporting
confidence: 78%
“…31) In our study, the level of renal MDA was increased in untreated diabetic mice compared to normal control group. UDCA treatment demonstrated its anti-lipid peroxidation activity.…”
Section: )supporting
confidence: 51%
“…Increases of IL-1 and IL-4 levels are induced by clinical and experimental diabetes [44,45]. The generation of ROS induced by hyperglycaemia plays a central role in the pathogenesis of diabetic neuropathy and brain oxidative injury [1] and these radicals can stimulate the production of cytokines [45,46]. It was also reported that diabetes-induced impairments in IL-1 signalling were linked to aberrant mitochondrial bioenergetics [42].…”
Section: Parametersmentioning
confidence: 99%
“…Two active steroidal lactones in Withania root extract are withaferin and withanolides (2). Some of therapeutics effects of Withania coagulans extract (WCE) have been reported by researchers (3)(4)(5). Upadhyay and et al reported antihyperglycemic effect of WCE in diabetic patients (1).…”
Section: Introductionmentioning
confidence: 99%